THE NARRATIVE OF PROTECTING POLYGAMOUS WOMEN IN INDONESIA'S DIGITAL WORLD: Between Moderate and Conservative Muslims - Hadi, Mukhammad Nur (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
This article focuses on the narrative of the polygamy issue on four Indonesian Islamic websites: portal-islam.id, nu.or.id, rumaysho.com, and muslim.or.id. They are selected based on ranking and visitation by referring to the results of processing data on similarweb. Deploying a content analysis approach, this article looks at the extent to which moderate and conservative school websites display the legal narrative of polygamy on their platforms. This research shows that there is a reasonably intense contestation between conservative and moderate perspectives on Islamic websites on the issue of polygamy. Both use the excuse of protecting women as the fundamental argument. Moderate Islamic website such as nu.or.id criticizes conservative understanding but also shows some views that align with traditional schools. The conservative Islamic websites: portal-islam.id, rumaysho.com, and muslim.or.id mostly stand firmly on the traditional argument, polygamy means protecting women. I argue that in this position, the moderate and the conservative Islamic websites, at the top of the rankings do not significantly impact the progressivity of the polygamy legal discourse movement in the digital discourse.[Artikel ini berfokus pada narasi isu poligami di empat situs web Islami Indonesia: portal-islam.id, nu.or.id, rumaysho.com, dan muslim.or.id. Mereka diseleksi berdasarkan ranking dan visitasi dengan mengacu pada hasil pengolahan data pada similarweb. Menggunakan pendekatan analisis konten, artikel ini melihat sejauh mana situs web Islami bernuansa moderat dan konservatif menampilkan narasi hukum poligami di platform mereka. Penelitian ini menunjukkan bahwa terdapat kontestasi antara perspektif konservatif dan moderat dalam situs web Islami tentang isu poligami. Keduanya menggunakan dalih melindungi perempuan sebagai argumen dasar. Situs web Islami beraliran moderat, yakni nu.or.id mengkritisi pemahaman konservatif, tetapi juga menunjukkan beberapa pandangannya berkelindan dengan aliran tradisional. Situs web Islami yang konservatif: portal-islam.id, rumaysho.com, dan muslim.or.id sebagian besar berdiri teguh pada argumen tradisional, yakni poligami berarti melindungi perempuan. Saya berargumen bahwa dalam posisi ini, situs-situs web Islami moderat dan konservatif, di peringkat teratas tidak berdampak signifikan terhadap progresivitas gerakan wacana hukum poligami dalam wacana digital.]